Effects of Season and Storage Period on Accumulation of Individual Carotenoids in Pumpkin Flesh (Cucurbita moschata) - Jaswir, I; Shahidan, N; Othman, R; Hashim, YZHY; Octavianti, F; bin Salleh, MN (Japan Oil Chemists Soc, 2024)
Indexed by SCOPUS/WOS